2021
DOI: 10.1186/s13223-021-00579-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lanadelumab in hereditary angioedema: a case series of 12 patients in Canada

Abstract: Background Hereditary angioedema (HAE) is a rare autosomal dominant disease resulting in recurring episodes of swelling, leading to considerable patient morbidity and mortality. Lanadelumab is a plasma kallikrein inhibitor that is approved as 1st line therapy in Canada for long term prophylaxis of HAE attacks. Objective To describe our clinical findings from a case series of adult patients with HAE type 1/2 who have been initiated on lanadelumab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…A recently updated understanding of angioedema helped to develop novel therapeutic options, especially lanadelumab and berotralstat, which target the upstream factors, accelerating bradykinin production. Lanadelumab is a human-specific monoclonal antibody targeting plasma kallikrein that acts as an inhibitor and reduces downstream bradykinin generation; several studies showed that lanadelumab potentiates the therapeutic preventive effect for angioedema development [29][30][31][32]. Berotralstat suppresses the development of angioedema by the inhibitory action of plasma kallikrein, subsequently decreases bradykinin production, and shows strong regulatory action for angioedema; this efficacy was confirmed by several clinical studies [33][34][35][36].…”
Section: Recent Advancement Of Angioedema Treatmentmentioning
confidence: 89%
“…A recently updated understanding of angioedema helped to develop novel therapeutic options, especially lanadelumab and berotralstat, which target the upstream factors, accelerating bradykinin production. Lanadelumab is a human-specific monoclonal antibody targeting plasma kallikrein that acts as an inhibitor and reduces downstream bradykinin generation; several studies showed that lanadelumab potentiates the therapeutic preventive effect for angioedema development [29][30][31][32]. Berotralstat suppresses the development of angioedema by the inhibitory action of plasma kallikrein, subsequently decreases bradykinin production, and shows strong regulatory action for angioedema; this efficacy was confirmed by several clinical studies [33][34][35][36].…”
Section: Recent Advancement Of Angioedema Treatmentmentioning
confidence: 89%
“…All our patients reported a significant improvement in the number of angioedema attacks per month, which is in line with previous real-life reports. 1 , 8 , 9 Moreover, over half of the patients experienced complete remission from attacks since starting lanadelumab. Patients also reported a significant improvement in their quality of life after starting lanadelumab.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Moreover, Iaboni et al reported that two-thirds of their patients reported no impact on social outings due to angioedema attacks, with only 1 patient having to miss work, after at least 6 months of lanadelumab. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Also, no patients aged ≥ 65 years were part of the treatment arms that included a lanadelumab dose of 300 mg. 5 In a case series of 12 patients in Canada, treatment with lanadelumab decreased angioedema attacks by mdedge.com/fedprac 72%. 9 However, the series only included 1 patient with type II HAE who was aged 36 years. 9 Therefore, our case demonstrates the efficacy of lanadelumab in a patient aged ≥ 65 years with type II HAE.…”
Section: Discussionmentioning
confidence: 99%